Impact of voltage sag on electrical system for water pumping of Mae Moh mine - W. Boonkird (2018)
© 2018 IEEE. This paper studies the voltage sag on a distribution system that delivers power to an array of water pumps in Mae Moh mine. Mae Moh mine is an open pit mine, therefore, electric pump is a crucial equipment for pumping water out of mine. DIgSILENT's PowerFactory software is used for modeling the electrical system and assessing the severity of voltage sag that is caused by sequential starting of large motors as this might affect some sensitive loads at various buses. Possible solutions are described for the worse cases where the voltage dip is considered unacceptable.